On the precipitation hardening of selective laser melted AlSi10Mg - Aboulkhair, Nesma T.; Tuck, Christopher; Ashcroft, Ian; Maskery, Ian; Everitt, Nicola M. (Springer, 2015)
Precipitation hardening of selective laser melted AlSi10Mg was investigated in terms of solution heat treatment and aging duration. The influence on the microstructure and hardness was established, as was the effect on the size and density of Si particles. Although the hardness changes according to the treatment duration, the maximum hardening effect falls short of the hardness of the as-built parts with their characteristic fine microstructure. This is due to the difference in strengthening mechanisms.